Laboratory-based simultaneous detection of residual xylazine and sedative-hypnotics from drugs-spiked beverages for forensic investigation - Koon, Teoh Way (2022)
Drug Facilitated Crimes (DFCs) involve the incapacitation of a victim due to the administration of a single drug or a combination of drugs. Xylazine, ketamine and benzodiazepines such as diazepam and nimetazepam are also the frequently used drugs in DFCs. Conventionally, biological samples are collected from a victim and analysed to provide evidence of drug administration. However, the rapid metabolism of many such drugs together with delays in analysis can compromise the detection of such drugs. Therefore, drugs-spiked beverages were suggested as evidence during DFC investigation. The present study was aimed to establish the analytical strategies for simultaneous detection of xylazine and sedative-hypnotics (diazepam, ketamine and nimetazepam) in drugs-spiked beverages appearing in liquid, droplet, and dry forms. In this study, chemical tests, attenuated total reflectance-Fourier transform infrared (ATR-FTIR) spectroscopy, gas chromatography (GC) and high-performance liquid chromatography (HPLC) detection were used and applied for the detection of the target substances from drugs-spiked beverage samples. Janovsky test allowed for the detection of diazepam ( 5 μg), ketamine ( 1 mg) and nimetazepam ( 5 μg). Xylazine could not be detected using the chemical tests. ATR-FTIR in couple with chemometric analyses enabled the discrimination of xylazine and sedative-hypnotics (diazepam, ketamine and nimetazepam), including those samples recovered from the dry beverage remains. GC method was established [limit of detection (LOD) (xylazine; 80 ng/mL; ketamine: 80 ng/mL; nimetazepam: 160 ng/mL); linearity (R2>0.99), precision (%RSD <7.20); accuracy (% recovery: 92.84 – 103.48%)] to detect target substances in spiked beverages remains. Satisfactory recoveries were achieved from drugs-spiked liquid (51.03% – 97.13%), droplet (48.27% – 95.91%) and dry (44.38% – 92.71%) samples through the application of developed GC method upon dispersive liquid-liquid microextraction (DLLME) procedure. A HPLC method was also established [LOD (xylazine: 39.1 ng/mL; diazepam: 78.1 ng/mL; ketamine: 156.3 ng/mL; nimetazepam: 78.1 ng/mL); linearity (R2>0.99), precision (%RSD <7.82); accuracy (% recovery: 95.31% - 106.56%)] and applied to detect target substances in spiked beverage remains. Good recoveries were achieved from the drug-spiked samples in liquid (64.21% – 105.43%), droplet (49.45% – 81.67%) and dry (47.24% – 88.27%) forms. However, only 13.33% of ketamine was able to be recovered from mineral water appearing in dry form. To conclude, analytical methods were successfully developed to simultaneously detect residual xylazine and other drugs of abuse (diazepam, ketamine, and nimetazepam) from spiked beverages. This study is beneficial to the law enforcement authorities during DFCs investigation, especially the determination of whether a sedative-hypnotic drug had been used.